Differential effects of transient constant light-dark conditions on daily rhythms of Period and Clock transcripts during Senegalese sole metamorphosis. (June 2013) - Martín-Robles, Águeda J.; Whitmore, David; Pendón, Carlos; Muñoz-Cueto, José A.
<x xml:space="preserve">Abstract</x> Studies on the developmental onset of the teleost circadian clock have been carried out in zebrafish and, recently, in rainbow trout and Senegalese sole, where rhythms of clock gene expression entrained by light-dark (LD) cycles have been reported from the first days post fertilization. However, investigations of molecular clock rhythms during crucial developmental phases such as metamorphosis are absent in vertebrates. In this study, we documented the daily expression profile of Per1, Per2, Per3, and Clock during Senegalese sole pre-, early-, middle-, and post-metamorphic stages under LD 14:10 cycles (LD group), as well as under transient exposure to constant light (LL-LD group) or constant dark (DD-LD group) conditions. Our results revealed that robust rhythms of clock genes were maintained along the metamorphic process, although with declining amplitudes and expression levels. All daily profiles were affected by transient constant conditions, in particular Per1, Per3, and Clock amplitudes and Per2 acrophase. Rhythm parameters were progressively restored upon reversion to LD cycles but even after 9 d under cycling conditions, a prolonged effect on clock function was observed, especially in the LL-LD group. These results reflect the differential sensitivity of clock machinery of sole to transitory light cues, being Per1 and Per3 predominantly clock regulated and supporting the role of Per2 as part of the light input pathway. Interestingly, there is no reversal in the phase of clock gene rhythms between pre- and post-metamorphic animals that would be coincident with the switch from diurnal to nocturnal locomotor activity, which occurs in this species just before the beginning of this process. Whether specialized central pacemakers dictate the phase of locomotor activity or this control is exerted outside of the core clock mechanism remains to be elucidated. Our results emphasize the importance of maintaining cycling light-dark conditions in aquaculture practices during ontogeny of Senegalese sole. (Author correspondence: munoz.cueto@uca.es or carlos.pendon@uca.es)